Estudo da adição do resíduo proveniente da extração de minério de ferro em argilas do Rio Grande do Norte - Chaves, Leonardo Flamarion Marques (2009)
The mining industry is responsible for the generation of waste from their natural process of extraction. The mining impacts in urban areas are of special importance due to the high urban occupation, which are exacerbated due to the proximity of the mined areas and populated areas. Some solutions to wastedisposal have the potential to significantly reduce the environmental risks and liabilities, but represent higher costs in the stages of deployment and operation. The addition of mining waste as raw material in the development of commercial products reduces the environmental impacts, transforming the waste into a positive element in the generation of employment and income. This thesis studies the incorporation of waste iron ore in two clays, one from the ceramic industry of the City of Natal and the other from the ceramic industry of the Seridó Region, both in the State of Rio Grande do Norte, Brazil. Percentages of iron ore waste of 5%, 10% , 15%, 20%, 25% and 30% were used in the tested ceramic matrix. The two clays and the iron ore waste used as part of this investigation were characterized by X-ray diffraction tests, X-ray fluorescence tests, differential thermal analysis, thermogravimetric analysis and dilatometric analysis. The samples were sintered under temperatures of 850 °C, 950 °C and 1050°C at a heating rate of 5 °C/min with isotherms of two hours. The following tests were performed with the samples: linear shrinkage, water absorption, apparent porosity, apparent density, mass loss in fire and bending resistance in order to obtain their physical and mechanical properties. An amount of 5% of waste iron ore in the matrix clay at a temperature of 850 0C resulted in na increase of about 65% in the tensile strength of the clay samples from the Natal ceramic industry. A linear shrinkage of only 0.12% was observed for the samples, which indicates that the physical properties of the final product were not influenced by the addition of the waste